Underlying mechanisms of ketotherapy in heart failure: current evidence for clinical implementations - Liu, Kun; Yang, Yang; Yang, Jing-Hua (Frontiers in Pharmacology, 2024)
Heart failure (HF) is a life-threatening cardiac syndrome characterized by high morbidity and mortality, but current anti-heart failure therapies have limited efficacy, necessitating the urgent development of new treatment drugs. Exogenous ketone supplementation helps prevent heart failure development in HF models, but therapeutic ketosis in failing hearts has not been systematically elucidated, limiting the use of ketones to treat HF. Here, we summarize current evidence supporting ketotherapy in HF, emphasizing ketone metabolism in the failing heart, metabolic and non-metabolic therapeutic effects, and mechanisms of ketotherapy in HF, involving the dynamics within the mitochondria. We also discuss clinical strategies for therapeutic ketosis, aiming to deepen the understanding of the characteristics of ketone metabolism, including mitochondrial involvement, and its clinical therapeutic potential in HF.